SAT0269 Efficacy and Safety of Anti-TNF Alpha in BehÇEt Disease: Preliminary Results of A French Multicenter Registry of 92 Patients. (10th June 2014) - Vallet, H.; Riviere, S.; Lambert, M.; Deroux, A.; Bielfeld, P.; Seve, P.; Fraison, J.B.; Perard, L.; Schoindre, Y.; Papo, T.; Kaplanski, G.; Sellam, J.; et al.
Abstract : Background: Behçet's disease (BD) is a systemic large vessel vasculitis with recurrent genital and oral ulceration, uveitis, cardio-vascular, joints, neurological or gut symptoms. Treatment of BD is dependent of the nature and the severity of clinical manifestations. Increased levels of TNF alpha and soluble TNF receptors have been found in the serum, plasma and in the aqueous humor of patients with BD. Although, anti-TNF alpha have proved effective in refractory uveitis, few data are available relative to its efficacy in extraocular manifestations of BD. Objectives: The aim of this study is to report on the efficacy and the safety of anti-TNF alpha in BD. Methods: We performed a retrospective multicenter study of main characteristics and outcomes of 92 patients with BD treated with anti-TNF alpha. Results: Ninety two observations were collected in 18 French centers. Mean ± SD age at the anti-TNF alpha introduction was 34±10 years with 55% of men. Seventy nine (79%) patients received at less one immunosuppressive therapy before the use of anti-TNF alpha. The main indications of anti-TNF alpha were uveitis (n=71, 77%), mucocutaneous manifestations (n=14, 15%) [oral (n=13) and genital ulcerations (n=5)], articular (n=12, 13%), neurologic (n=7, 8%), cardio-vascular (n=4, 4%) and digestive manifestations (n=3, 3%). Infliximab was frequently used (60%), followed by adalimumab (35%), etanercept (4%) and golimumab (1%). Associated therapy included prednisolone (82%), azathioprine (30%), mycophenolate mofetil (6%), and methotrexate (5%). Median duration of follow up was 32 months [10-57]. 96% and 92% of BD patients achieved a complete or partial response of uveitis and extraocular manifestations, respectively. Anti-TNF alpha had a significant corticosteroid sparing effect (daily prednisolone dose of 40mg at time of introduction of anti-TNF alpha vs 10mg and 5mg at 6 and 12 months, respectively; p<0, 0001). The median time for clinical improvement was 61 days [31-92]. Adverse events were reported in 26% of patients, mainly with infliximab. They included infections (19%), hypersensitivity reactions (2%), injection site reactions (2%), cancers (2%) and lupus (1%). Serious adverse events were reported in 8 patients (of whom 7 with infliximab) and required treatment interruption in all cases. Conclusions: These preliminary results show that TNF alpha inhibitors are highly and rapidly efficient in all BD manifestations. Although tolerance seems satisfactory, infliximab is associated with more frequent and more serious side effects. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5903